2017
DOI: 10.3389/fpls.2017.01632
|View full text |Cite
|
Sign up to set email alerts
|

Root Traits, Nodulation and Root Distribution in Soil for Five Wild Lentil Species and Lens culinaris (Medik.) Grown under Well-Watered Conditions

Abstract: The efficient use of resources such as water and nutrients by plants is increasingly important as the world population food demand continues to grow. With the increased production of lentil in the temperate zones of North America, improvement in yield needs to be maintained. The use of wild lentil genotypes as sources of genetic diversity for introgression into cultivated lentil is an important breeding strategy, but little is known about their root systems. We evaluated the root systems of five wild lentil sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…orientalis (Ferguson et al, 1998; Gupta & Sharma, 2006). Variation in root traits, including nodulation and root distribution in soil differences, were discovered in wild Lens taxon ( L. orientalis , L. tomentosus , L. odemensis , L. lamottei , L. ervoides ) that may be useful for breeding increased biomass or seed production (Gorim & Vandenberg, 2017a). Identification of novel sources of extra earliness from a wild accession, ILWL118, having less than 90 days maturity has resulted in the development of extra early breeding lines.…”
Section: Lentilmentioning
confidence: 99%
“…orientalis (Ferguson et al, 1998; Gupta & Sharma, 2006). Variation in root traits, including nodulation and root distribution in soil differences, were discovered in wild Lens taxon ( L. orientalis , L. tomentosus , L. odemensis , L. lamottei , L. ervoides ) that may be useful for breeding increased biomass or seed production (Gorim & Vandenberg, 2017a). Identification of novel sources of extra earliness from a wild accession, ILWL118, having less than 90 days maturity has resulted in the development of extra early breeding lines.…”
Section: Lentilmentioning
confidence: 99%
“…We found the significant variation, medium to high heritability, approximately normal distribution and significant correlations for these root traits. Although, genetic variation of root system vary from plant to plant, the presence of very fine roots (<0.5 mm diameter) and fine roots (0.5 to 2.0 mm) determines the most percentage of root traits is important for nutrient and water uptake [61][62][63]. In this study, we identified the high percentage of fine roots with diameter from 0.5 to 2.0 mm in LP compared to NP conditions, while percentage of very fine roots with <0.5 mm diameter more in NP condition.…”
Section: Discussionmentioning
confidence: 99%
“…For metabolomic analysis at flowering stage, just after uprooting the plants in the field, approximately 100‐mg freshly collected nodules were immediately frozen in liquid nitrogen and stored in −80°C until analysis. Each time, roots and nodules were collected from the harvested area using soil cores (10‐cm diameter) to 40‐cm depth, because 90% of the lentil root biomass and nodules is in the top 40 cm soil depth (Gorim & Vandenberg, ). The cores were kept on ice after excavation (except maturity samples) and brought to the laboratory, then rinsed with tap water and soaked in 0.01 M CaCl 2 solution for 5 min to remove clay particles and desorb nutrients from the root surface.…”
Section: Methodsmentioning
confidence: 99%
“…In and nodules were collected from the harvested area using soil cores (10-cm diameter) to 40-cm depth, because 90% of the lentil root biomass and nodules is in the top 40 cm soil depth (Gorim & Vandenberg, 2017 cv. Yitpi) grown as a non-N 2 fixing reference adjacent to lentil plots was also sampled.…”
Section: Experimental Site and Designmentioning
confidence: 99%